Peningkatan Pemahaman Anggota Federasi Serikat Pekerja Kahutindo Kota Pekanbaru Tentang Regulasi Pengupahan - Zulkarnaen Noerdin; Robert Libra Robert (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
The need for an understanding of Increasing Understanding of the Government Regulation of the Republic of Indonesia Number 78 of 2015 concerning Wages at the Kahutindo Pekanbaru Workers Union is very urgent. This activity was carried out on December 30, 2021 at Ayam Penyet Pak Tisto Rumbai Pekanbaru in the form of lectures, dialogues and discussions to solve the problems faced. The work procedure to support the method offered is that lectures are held for 1 (one) hour, and dialogue and discussion for 2 hours or according to the needs of partners as long as they are still within the period of implementing this program. The output that will be produced according to the plan for community service activities is: for partners, of course, an increase in understanding of the Government Regulation of the Republic of Indonesia Number 78 of 2015 concerning Wages.